2015
DOI: 10.1155/2015/281756
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miR-378a in Metabolism, Angiogenesis, and Muscle Biology

Abstract: MicroRNA-378a (miR-378a, previously known as miR-378) is one of the small noncoding RNA molecules able to regulate gene expression at posttranscriptional level. Its two mature strands, miR-378a-3p and miR-378a-5p, originate from the first intron of the peroxisome proliferator-activated receptor gamma, coactivator 1 beta (ppargc1b) gene encoding PGC-1β. Embedding in the sequence of this transcriptional regulator of oxidative energy metabolism implies involvement of miR-378a in metabolic pathways, mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 133 publications
3
83
0
Order By: Relevance
“…Growing evidence has demonstrated that miR-378a-3p is involved in a wide range of biological functions and processes such as cell growth, cell cycle, migration, differentiation, metabolism and angiogenesis [12,15]. A recent study shows that miR-378a-3p, a negative regulator of TGFβ1, contributes to the suppression of cardiac fibrosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has demonstrated that miR-378a-3p is involved in a wide range of biological functions and processes such as cell growth, cell cycle, migration, differentiation, metabolism and angiogenesis [12,15]. A recent study shows that miR-378a-3p, a negative regulator of TGFβ1, contributes to the suppression of cardiac fibrosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to myomiRs, previous studies have revealed the roles of other abundantly expressed miRNAs in skeletal myogenesis. For example, miR-378-3p could increase the expression of MyoD by repressing MyoR in myoblast cells [39]; miR-424 promoted C2C12 myoblast differentiation via direct targeting of the 3´UTR of Cdc25A [40]. Ge et al [41] have reported that miR-125b-5p negatively modulated muscle regeneration in mice, while IGF-2 is a direct target of miR-125b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of muscle development often explore gene expression under different conditions (Krist et al, 2015; Wang, Xiao & Wang, 2016; Zhang et al, 2016a; Zhang et al, 2015). The expressions of most genes display variable expression levels in prenatal and postnatal periods, and reference genes that are frequently used for other experiments are not suitable for studies of skeletal muscle development.…”
Section: Introductionmentioning
confidence: 99%